2020
DOI: 10.3390/nu12092509
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid and Vascular Damage in Essential Hypertension: Role of Insulin Resistance

Abstract: Increased levels of uric acid (UA) have been shown to be correlated with many clinical conditions. Uric acid may adversely affect the insulin signalling pathway inducing insulin resistance (IR). Several studies report the association between arterial stiffness (AS), an early indicator of atherosclerosis, and UA. The purpose of the present study was to evaluate the association between UA and AS, considering the potential role of IR. We enrolled 1114 newly diagnosed, never-treated hypertensive patients. Insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…e present study finds that, under a long-term high-pressure environment, ß cells initially mount a compensatory response to ramp up ß cell functional capacity and insulin secretion to meet the elevated pressure demand. Other studies have found that insulin resistance leads to arterial stiffness [13,14,31]. e outcome of the abovementioned mechanisms is increased insulin secretion.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…e present study finds that, under a long-term high-pressure environment, ß cells initially mount a compensatory response to ramp up ß cell functional capacity and insulin secretion to meet the elevated pressure demand. Other studies have found that insulin resistance leads to arterial stiffness [13,14,31]. e outcome of the abovementioned mechanisms is increased insulin secretion.…”
Section: Discussionmentioning
confidence: 98%
“…Several factors are believed to be responsible for arterial stiffness, including age, hypertension, and hyperglycemia. Studies have found that insulin resistance is significantly associated with arterial stiffness [13,14]. Euglycemic hyperinsulinemic clamp studies have revealed a relationship between insulin resistance and arterial stiffness in both young, healthy women and diabetic adults [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The estimation of sample size requirements was performed with the program Quanto (version 1.2) and based upon previously reported data obtained in populations similar to ours. To compute our model we assumed an average cfPWV between 6.7 and 7.5 m/s, with a standard deviation (SD) ranging between 1.8 and 2.5 m/s (37,38), and a minimum minor allele frequency = 4.5% (31)(32)(33). In order to be able to detect a clinically relevant difference in cfPWV between genotypes according to a dominant model [at least 1 m/s (13, 39)], with two-sided α = 0.05 and β = 0.80, the recommended sample size was equal to 607 subjects.…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential antihypertensive mechanisms of dietary fiber intake have not been elucidated until now. Insulin resistance has been found to be associated with the development of hypertension, and dietary fiber intake might improve blood pressure by modulating insulin metabolism ( 26 , 27 ). Reduced levels of serum cholesterol are associated with improved endothelial function, which mediates vasodilation and reduces blood pressure ( 28 30 ).…”
Section: Discussionmentioning
confidence: 99%